Hubungan Pengasuhan Orang Tua dengan Risiko Tindak Kekerasan pada Remaja di Kelurahan Patrang Kecamatan Patrang Kabupaten Jember (The Correlation of Parenting with Risk of Juvenile Violent in Patrang Village District Patrang Jember) - Rizal Pamungkas C. Yulianto; Iis Rahmawati; Lantin Sulistyorini (Pustaka Kesehatan, 2014)
Violence was an incident of physical injury, mental and sexual abuse were commonly made bypeople who have a responsibility for the wellnes of the children who was indicated by loss andthreats to the health and wellnes of the child . The purpose of this study was to determined thecorrelation of parenting with violence risk of adolescents in the Village District of PatrangPatrang Jember . The design of this study was used observational analytic design with crosssectional approach . This research was used 92 respondents as a sample by using purposivesampling . The results of the study was showed 50 parents did a good parenting and 62 juvenile(67,4%) didn’t have a violent risk. The Analyzed used chi - square 95 % CI ( α = 0.05), withodds ratios got p value 0.025 < α ( 0.05), and odds ratio ( OR ) 2.929 as the result . Theconclusion of the study was that there a correalation between parenting with the risk of violencein adolescents and the good parenting shall be have 2,929 times chance for decrease the riskof violence in juvenile than the didn’t one.Keywords: parenting , violence , juvenile